Analisis Hubungan Sedimen, Sampah Dan Parameter Hidraulik Terhadap Fluktuasi Debit Air Pada Saluran Irigasi Sekunder Bendungan Sidoras - A Simamora; L J Situmeang; J P Purba; Y Y Sitepu (Cered Indonesia Institute, 2026)
This study aims to analyze the relationship between sedimentation, waste, and hydraulic parameters on water discharge fluctuations in the Sidoras Dam secondary irrigation channel in Percut Sei Tuan sub-district. The hydraulic parameters analyzed include channel width, water depth, water velocity, cross-sectional area, and water discharge. This study uses a quantitative descriptive method with direct data collection in the field on seven observation segments along 2.5 km. Measurements were carried out using the floating method to determine flow velocity. Width and depth were measured using a meter. The results showed that the channel width ranged from 3.10 to 4.98 m with an average of 3.67 m. The flow depth varied between 0.63 to 1.625 m with an average of 0.812 m. The flow velocity was between 0.36 to 0.48 m/s with an average of 0.41 m/s. The water discharge ranged from 0.83 to 2.57 m³/s, with an average of 1.28 m³/s. The highest discharge was found in Segment 1 due to its large cross-sectional area and relatively clean channel conditions. Conversely, the smallest discharge was in Segment 5 due to channel narrowing, sedimentation, weeds, and garbage accumulation that obstructed water flow. The analysis results showed that changes in hydraulic parameters, sediment, and garbage had a strong relationship to water discharge fluctuations. The larger the cross-sectional area and flow velocity, the greater the water discharge tends to be. Conversely, channel silting and blockages lead to a decline in flow quality. Therefore, regular channel maintenance, such as sediment dredging, garbage removal, and weed control, is essential to maintain smooth irrigation water distribution and improve irrigation system efficiency.